Caracterização da cadeia produtiva de pequenas frutas nos Campos de Cima da Serra sob a ótica da produção e comercialização - Bizotto, Beatriz Lucia Salvador (My University, 2014)
To know and understand a supply chain it is necessary to know the connections and relationships between stakeholders and to identify the strengths and weaknesses of the chain. Since 2001 the sector of small fruits started to have an increase in cultivated area in the Campos de Cima da Serra area. The fruits that are part of this study are blackberries, raspberries, Mertilo, Strawberry, and Phisalys. This is presented as a new alternative for farmers who did not continue with the production process of the apple. Since 2001 the sector of Small Fruits of Campos de Cima da Serra had an increase in cultivated area. This expansion of small fruits in the Campos de Cima da Serra area has an explanation that goes beyond the simple logic of the market based on supply and demand. The climate ensures a reserve of natural market for the region, since the species demands low temperatures in its development. It only reaches the best quality if exposed for long term at low temperatures. There is unanimity among all stages of the production that this segment has the potential to redraw the region's economic profile In this context we started with the following questions: How is set up the chain of production of small fruits in the Campos de Cima da Serra? What are the positions of wholesalers and farmers? What are the relationships of the past situation, current and future small fruit? In this context, the objective was to perform a general diagnosis of the productive chain of small fruits in the region of Campos de Cima da Serra. We performed an exploratory research operationalized through a case study. As a tool for data collection were interviews with agents used in the production chain, ie, wholesalers and producers of small fruits. The main results of the characterization of small fruit production chain from the perspective of production and marketing, the positioning of wholesale and farmers interviewed regarding the chain of small fruits, as well as identifying the situation, past, present and future of small fruit in fields up the mountain. Among the main results we present a characterization of small fruit production chain from the perspective of production and marketing, positioning and wholesaler interviewed farmers about the chain of small fruits as well as the identification of the situation past, present and future of small fruits in Campos de Cima da Serra.
Para conhecer e entender uma cadeia produtiva é preciso que haja uma compreensão dos elos e relacionamentos que ocorrem entre os agentes envolvidos, para identificar os pontos fortes e fracos que compõem essa cadeia. A partir de 2001 o setor das Pequenas Frutas dos Campos de Cima da Serra teve um aumento na área de cultivares. As Frutas que fazem parte deste estudo são Amora, Framboesa, Mertilo, Morango, e Phisalys. Isso se apresentou como uma nova alternativa para os produtores rurais que não continuaram com o processo produtivo da maçã. Esta expansão das Pequenas Frutas nos Campos de Cima da Serra é justificada pela lei de oferta e procura. O clima garante uma reserva de mercado natural para a região, já que as espécies são exigentes em frio para seu desenvolvimento e só alcançam qualidade se forem expostas por longo prazo a baixas temperaturas. Há unanimidade entre todas as etapas da cadeia produtiva que o segmento tem potencial para redesenhar o perfil econômico da região com uma nova cadeia produtiva. Neste contexto partiu-se dos seguintes questionamentos: como está configurada a cadeia de produção de Pequenas Frutas nos Campos de Cima da Serra? Quais os posicionamentos dos atacadistas e produtores rurais? Quais as relações da situação passada, atual e futura das Pequenas Frutas? Neste contexto, o objetivo geral foi realizar um diagnóstico da cadeia produtiva de Pequenas Frutas na Região dos Campos de Cima da Serra. Foi realizada uma pesquisa exploratória operacionalizada através de um estudo de caso. Como ferramenta de coleta de dados foi utilizada entrevistas com os agentes da cadeia produtiva, ou seja, com atacadistas e produtores de Pequenas Frutas. Dentre os principais resultados apresenta-se uma caracterização da cadeia produtiva de pequenas frutas sob a ótica da produção e comercialização, o posicionamento do atacadista entrevistado e dos produtores rurais em relação à cadeia de pequenas frutas, bem como a identificação da situação passada, presente e futura das pequenas frutas nos Campos de Cima da Serra.
Keywords: Agroindústria - Campos de Cima da Serra (RS); Frutas - Cultivo - Rio Grande do Sul; Fruticultura; Pequenas frutas; Cadeia produtiva; Agronegócio; Orcharding; Small fruits; Production chain; Agribusiness